Digital empathy and adolescent social media behavior: Insights from a systematic review for counseling practice in Indonesia - Irfan Fahriza; Siti Cahyati; Syari Fitrah Rayaginansih; Muhammad Sidiq Permana; Ervina Rahma Agustina (Universitas Negeri Yogyakarta, 2025)
Indonesian adolescents who spend much of their social lives on social media face fear of missing out, pressure to curate idealized selves, and growing exposure to cyberbullying. Against this backdrop, the ability to recognize what others feel and to respond with care in screen-mediated interaction, digital empathy becomes a competency that school guidance and counseling can no longer treat as optional. This review asks three questions: which guidance and counseling interventions have been used to build digital empathy in Indonesian adolescents, where those interventions concentrate their efforts, and what their patterns imply for school counseling practice. Following PRISMA 2020 procedures, we searched Scopus, SINTA, Garuda, and Google Scholar for Indonesian-context publications from 2020 to 2025; after removing duplicates, screening titles and abstracts, checking full texts against eligibility criteria, and appraising quality, seven studies entered a thematic narrative synthesis. Across the seven studies, promising interventions weave together three strands: ethical digital citizenship, emotional literacy, and interactive media-based learning delivered through digital ecopedagogy, virtual group guidance, animated and comic-based media, and digital counseling services. Digital empathy emerges in a dual role: it works preventively against cyberbullying and developmentally as a foundation for emotional literacy. The review offers a counseling-specific map of this emerging field and argues for embedding digital ethics education.